Legal Framework and Practical Effectiveness of Prenuptial Agreements in Indonesian Marriages - Khairun Nisa, Raden Roro Salma Almira; Tjempaka, Tjempaka (Jurnal Hukum Magnum Opus, 2025)
In the context of marriage in Indonesia, the term "Prenuptial Agreement" is recognized as an important legal instrument that regulates the rights and obligations between husband and wife before a marriage takes place. This instrument is designed to protect the individual economic interests of each spouse by specifically arranging both premarital assets and assets acquired during the marriage. This study aims to analyze the legal framework regarding prenuptial agreements in Indonesia and its role in post-marital life, particularly concerning asset division, dispute resolution, and protection of the economic rights of spouses. It also assesses the extent to which the current legal framework is adequate in addressing increasingly complex social and economic changes, and how the implementation of prenuptial agreements is applied in Indonesia. This study examines the relevant legal provisions through a normative juridical research method. The findings show that prenuptial agreements have legitimate legal force and are recognized by the state. These agreements provide legal security for couples in terms of asset distribution and financial obligations and can minimize potential disputes in the future. Additionally, prenuptial agreements serve as a preventive instrument that protects each party's financial interests. Substantively, the effectiveness of prenuptial agreements is influenced by clear and fair provisions concerning the rights and obligations of the spouses. Structurally, the agreement must be drafted and executed in compliance with applicable legal requirements. With a well-structured prenuptial agreement, couples can obtain optimal legal protection, thereby minimizing the potential for conflicts regarding economic rights within marriage.